2015
DOI: 10.1109/ted.2015.2428613
|View full text |Cite
|
Sign up to set email alerts
|

Dispersive Effects in Microwave AlGaN/AlN/GaN HEMTs With Carbon-Doped Buffer

Abstract: Aluminium gallium nitride (AlGaN)/GaN high-electron mobility transistor performance is to a large extent affected by the buffer design, which, in this paper, is varied using different levels of carbon incorporation. Three epitaxial structures have been fabricated: 1) two with uniform carbon doping profile but different carbon concentration and 2) one with a stepped doping profile. The epitaxial structures have been grown on 4H-SiC using hot-wall metal-organic chemical vapor deposition with residual carbon dopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 29 publications
(29 reference statements)
1
25
0
Order By: Relevance
“…The pinch‐off voltage of the GaN‐on‐SiC is −4 V; while its value for the GaN‐on‐Si is equal to −3 V. The higher traps induced back‐gating for the GaN‐on‐Si reduces the required negative voltage to pinch‐off the channel. This has been also reported in Reference , which showed that higher concentration of the buffer traps will shift up the pinch‐off voltage. The impact of higher trapping in GaN‐on‐Si with respect to GaN‐on‐Dia has been also reported in Reference and summarized in Table .…”
Section: Simulation and Measurement Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The pinch‐off voltage of the GaN‐on‐SiC is −4 V; while its value for the GaN‐on‐Si is equal to −3 V. The higher traps induced back‐gating for the GaN‐on‐Si reduces the required negative voltage to pinch‐off the channel. This has been also reported in Reference , which showed that higher concentration of the buffer traps will shift up the pinch‐off voltage. The impact of higher trapping in GaN‐on‐Si with respect to GaN‐on‐Dia has been also reported in Reference and summarized in Table .…”
Section: Simulation and Measurement Resultssupporting
confidence: 79%
“…As can be seen, the GaN‐on‐Si device shows lower current levels with respect to the GaN‐on‐SiC. Also the effect of back‐gating potential due to buffer traps is clear from the different pinch‐off voltages of these devices. The pinch‐off voltage of the GaN‐on‐SiC is −4 V; while its value for the GaN‐on‐Si is equal to −3 V. The higher traps induced back‐gating for the GaN‐on‐Si reduces the required negative voltage to pinch‐off the channel.…”
Section: Simulation and Measurement Resultsmentioning
confidence: 89%
“…It was demonstrated that the carbon profile could be tuned so that the trap density close to the two-dimensional electron gas (2DEG) was reduced, while still demonstrating HEMTs with low leakage currents and small dispersive effects. 8 However, the growth process tuning involved changes in growth temperature, which can result in poor epitaxial layer uniformity and structural quality, as well as particle down falls during temperature transition.…”
Section: à3mentioning
confidence: 99%
“…It is clear that when an optimized process window for GaN is used during growth of the entire carbon doped buffer layer, the structural quality exceeds that when process tuning is used. 8 This allows the use of a gaseous carbon source even for very high carbon doping. The rocking curve of the AlN (0002) reflection has a FWHM value of 240 arcsec.…”
Section: à3mentioning
confidence: 99%
See 1 more Smart Citation